2013
DOI: 10.1185/03007995.2013.834250
|View full text |Cite
|
Sign up to set email alerts
|

Increasing awareness of hypoglycaemia in patients with Type 2 diabetes treated with oral agents

Abstract: Hypoglycaemia is the most common acute complication of type 2 diabetes and can limit therapeutic efforts to improve glycaemic control in order to protect against long-term complications. It is a potential side effect of the drugs used to treat diabetes, specifically exogenous insulin or insulin secretagogues. As many people are prescribed these agents, hypoglycaemia is frequent in clinical practice, although patients commonly do not inform their healthcare professional of the problems spontaneously. The impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 73 publications
1
12
0
Order By: Relevance
“…The ultimate goal of glycaemic management in both type 1 (T1D) and type 2 diabetes (T2D) is achievement of individualized glycaemic goals without hypoglycaemia, which remains a common and acute complication with antidiabetic medications, particularly exogenous insulin therapy. In T1D and T2D, hypoglycaemia can limit the glycaemic control that patients achieve and, therefore, undermine the goal of preventing long‐term complications . Furthermore, hypoglycaemia has a well‐established significant negative impact on well‐being, productivity and quality of life (QOL) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ultimate goal of glycaemic management in both type 1 (T1D) and type 2 diabetes (T2D) is achievement of individualized glycaemic goals without hypoglycaemia, which remains a common and acute complication with antidiabetic medications, particularly exogenous insulin therapy. In T1D and T2D, hypoglycaemia can limit the glycaemic control that patients achieve and, therefore, undermine the goal of preventing long‐term complications . Furthermore, hypoglycaemia has a well‐established significant negative impact on well‐being, productivity and quality of life (QOL) .…”
Section: Introductionmentioning
confidence: 99%
“…In T1D and T2D, hypoglycaemia can limit the glycaemic control that patients achieve and, therefore, undermine the goal of preventing long-term complications. [1][2][3][4][5] Furthermore, hypoglycaemia has a well-established significant negative impact on well-being, productivity and quality of life (QOL). 6 Recent studies have confirmed that, in addition to decreased overall health-related QOL, hypoglycaemia can negatively impact physical and mental well-being, limit mobility, lead to anxiety and depression, interfere with social activities, result in missed work (absenteeism), impair performance while at work (presenteeism) and decrease overall work productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Insulin therapy is associated with a high risk of hypoglycemia [29][30][31] . In contrast, incretin therapy is associated with a low risk of hypoglycemia [30,31,[39][40][41][42][43][44][45][46][47] . This is because the islet effect of GLP-1 is glucose dependent [7,9] and the glucagon counter-regulation to hypoglycemia is preserved or augmented [48][49][50] .…”
Section: Hypoglycemiamentioning
confidence: 84%
“…Hypoglycemia is associated with negative impact, such as unpleasant and sometimes dangerous symptoms, weight gain (due to defense eating), deterioration of glycemic control (due to reduced adherence to therapy and therapeutic goals because of fear of new hypoglycemic episodes), increased cardiovascular risk and increased risk for microvascular complications [38][39][40][41] . Insulin therapy is associated with a high risk of hypoglycemia [29][30][31] .…”
Section: Hypoglycemiamentioning
confidence: 99%
“…8 The researchers did not examine HbA1c control in the patients who stopped SMBG or monitor hypoglycaemia; however, in those people known to be at risk of hypoglycaemia, there is a need to improve use of SMBG as it is poorly implemented by both clinicians and patients. 25 Hypoglycaemia is a very serious adverse effect of treatment, remains one of the most common causes of admission to hospital from adverse drug effects, and is associated with increased mortality. There is no consistent trial evidence that this is reduced by routine monitoring in type 2 diabetes, 12 although it is of importance on a case-by-case basis.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%